The Effect of Environmental Education and Plastic Waste Management on Ecological Awareness and Pollution Reduction in Jakarta (West Science Interdisciplinary Studies, 2024)
This study examines the impact of environmental education and plastic waste management on ecological awareness and pollution reduction in Jakarta. Employing a quantitative research design, data were collected from 190 respondents through a structured questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results reveal that both environmental education and plastic waste management significantly enhance ecological awareness, which in turn drives pollution reduction. Plastic waste management also exhibits a strong direct effect on pollution reduction, highlighting its critical role in mitigating environmental degradation. These findings underscore the importance of integrating educational programs with effective waste management systems to foster sustainable urban development. The study provides actionable insights for policymakers, educators, and environmental practitioners in addressing Jakarta’s pressing environmental challenges.